1998
DOI: 10.1016/s0014-5793(98)00806-0
|View full text |Cite
|
Sign up to set email alerts
|

Profile of protein kinase C isozymes and their possible role in mammalian egg activation

Abstract: Western blot analysis was used to investigate protein kinase C (PKC) profile of rat eggs. The presence of eight PKC isozymes was demonstrated: conventional PKC K K, L L and Q Q; novel PKC N N, O O and W W; atypical PKC j j and V V. PKC K K was detected by RT-PCR as well. PKC translocation from the cytosol to the plasma membrane served as a marker for enzyme activation. Immunofluorescence confocal microscopy demonstrated a relatively uniform distribution of PKC K K, L LI, and L LII throughout the cytosol of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
(48 reference statements)
2
31
0
Order By: Relevance
“…Luria et al (2000) demonstrated the activation of PKC-a aPKC-b 1 in fertilized mouse oocytes. Raz et al (1998) observed relocalization of cPKC isotypes PKC-a and PKC-b during activation of rat oocytes. Fan et al (2002b) observed PKC-a, b 1 and g in matured pig oocytes and described the relocalization of these PKCs after oocyte fertilization or oocyte parthenogenetic activation using calcium ionophore A23187.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Luria et al (2000) demonstrated the activation of PKC-a aPKC-b 1 in fertilized mouse oocytes. Raz et al (1998) observed relocalization of cPKC isotypes PKC-a and PKC-b during activation of rat oocytes. Fan et al (2002b) observed PKC-a, b 1 and g in matured pig oocytes and described the relocalization of these PKCs after oocyte fertilization or oocyte parthenogenetic activation using calcium ionophore A23187.…”
Section: Discussionmentioning
confidence: 74%
“…Various authors have detected calcium-dependent isotypes PKC-a, -b I , -b II , -g; calcium-independent isotypes PKC-d, -e, -m, or atypical isotypes PKC -l and -z in matured rodent oocytes (Gangeswaran and Jones, 1997;Raz et al, 1998;Luria et al, 2000;Pauken and Capco, 2000;Downs et al, 2001;Eliyahu and Shalgi, 2002;Viveiros et al, 2003). However, the data concerning the spectra of PKC isotypes are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that CGE, a major process in preventing polyspermy, can be triggered either by [Ca 2C ] i rise or by PKC activation (Gangeswaran & Jones 1997, Johnson & Capco 1997, Raz et al 1998a,1998b, Luria et al 2000, Pauken & Capco 2000. We have previously demonstrated that upon egg activation, MARCKS could either be phosphorylated by activated PKC or be bound by Ca 2C -activated CaM (Eliyahu et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ca 2C -dependent and Ca 2C -independent PKC isoforms were identified in rodent eggs (Gangeswaran & Jones 1997, Raz et al 1998b. The change in the intracellular distribution of various PKC isoforms, as manifested by its translocation from the cytoplasm to the plasma membrane of the egg, was followed during fertilization as well as during parthenogenetic activation of eggs (Gallicano et al 1995.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation